(untitled) (Revista Científica Integrada, 2025)
Objective: To understand community health workers’ perceptions of their work in the Family Health Strategy. Methods: This observational study involved 17 community health workers affiliated with Family Health Strategy teams. Data were collected from August 2022 to March 2023 through semi-structured interviews. Quantitative data were analyzed using descriptive statistics, and qualitative data were classified using the Descending Hierarchical Classification (DHS) system, supported by Iramuteq software. Results: Based on the community health workers’ reports, it was found that their perceptions of their work are interconnected with social, health, structural, and environmental aspects, revealing factors that influence both the development of care actions and their own health. Therefore, based on semantic similarity, three categories were defined: Community Health Workers’ Work, Use of Personal Protective Equipment, and Perceived Occupational Risks. Conclusion: The perceptions of community health workers reflect the challenging reality faced in the region, characterized by a context of high social vulnerability and exposure to occupational hazards. The reports highlight organizational and environmental factors that directly impact professional practice, reinforcing the need for effective interventions to contribute to their mitigation.